Immune repertoire profiling and T cell dysregulation in Peripheral Blood Mononuclear Cells of Type 2 diabetic patients - Zheng Bi; Fanjing Wang; Shengmao Wang; Zhaohui Fang (PLoS ONE, 2025)
Objective The prevalence of diabetes mellitus (DM) is escalating globally, presenting a significant public health challenge. The immune system, particularly T cells, plays a crucial role in the pathogenesis of diabetes. This study aims to elucidate the characteristics of T cell receptors (TCRs) and immune dysregulation within peripheral blood mononuclear cells (PBMCs) of diabetic patients, with exploratory analysis of microbial profiles. Methods We employed high-throughput RNA-seq to analyze the protein-coding genes expression, and function enrichment with different expression, BCR/TCR repertoires and microbial communities in PBMC samples collected from both diabetic patients and healthy controls. Comparative analysis was conducted to identify distinct TCR signatures associated with diabetes. Microbial communities were secondarily assessed via unmapped RNA-seq reads. Results Overall, we found different patterns of gene expression, gene function, immune cell proportion, immune repertoire and microbiome between the different DM and control groups. 1145 upregulated 400 down-regulated genes were identified, and immune response function terms were enriched, such as, cell-cell adhesion via plasma-membrane adhesion molecules, and homophilic cell adhesion via plasma membrane adhesion molecules (BP); as well as in the T cell receptor complex, plasma membrane signaling receptor complex, alpha-beta T cell receptor complex (CC), and in antigen binding and immunoglobulin receptor binding (MF). Furthermore, reactome pathway enrichment analysis revealed enrichment of these DEGs in Viral mRNA Translation, Influenza Viral RNA Transcription and Replication, SARS-CoV-1 modulates host translation machinery, Interleukin-6 family signaling, etc. DM PBMC showed significantly lower chao1 index of TCR (including TCRA and TCRB) and reduced expression of TRAV/TRBV genes compared to controls. Enriched pathways included T cell receptor complex, antigen binding, and interleukin-6 signaling. Exploratory analysis of microbial reads revealed decreased alpha diversity (chao1/ACE) in DM and 123 altered taxa, though microbial abundance was low. Conclusion Our study provides novel insights into T cell receptor dysregulation in diabetes. The role of PBMC-associated microbiota requires further validation.